Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and characterization of Fusarium spp. associated with wheat grains

Abstract: Thirty one isolates belonging to six fungal genera were found to be associated with wheat grain samples collected from three main regions in Saudi Arabia. The most common genera (average frequency) were Aspergillus (19.52%), Fusarium (32.31%), Penicillium (12.19%), and Alternaria (8.2%). In this study, different isolates of Fusarium spp. were isolated from wheat grains samples and identified at the molecular level by ITS-rDNA regions amplification. Twenty five isolates of Fusarium spp. were screened for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the present study, a Fusarium solani isolate was morphologically identified and confirmed by PCR using specific primers from the ITS region. Fusarium species are difficult to identify because they are similar and it is important to use molecular methods to differentiate taxa (Mahmoud and Shehata, 2017). The two metabolites evaluated showed antioxidant properties.…”
Section: Antimicrobial Activity Of Secondary Metabolitesmentioning
confidence: 99%
“…In the present study, a Fusarium solani isolate was morphologically identified and confirmed by PCR using specific primers from the ITS region. Fusarium species are difficult to identify because they are similar and it is important to use molecular methods to differentiate taxa (Mahmoud and Shehata, 2017). The two metabolites evaluated showed antioxidant properties.…”
Section: Antimicrobial Activity Of Secondary Metabolitesmentioning
confidence: 99%
“…Aflatoxins are secondary metabolites produced by fungi species from the genus Aspergillus, notably A. flavus, A. parasiticus and A. nomius, which develop naturally in food products and cause a wide array of toxic effects in several animal species, including humans [1]. Aflatoxins are typically reported in dry food commodities (cereals, spices, nuts and dry fruits), while the metabolic products of aflatoxins, such as AFM1 and AFM2, are reported in milk [2,3]. Aflatoxin is a mycotoxin produced by two types of Aspergillus which are Aspergillus flavus and Aspergillus parasiticus.…”
Section: Introductionmentioning
confidence: 99%